Eksplorasi Dan Inventarisasi Anggrek Di Desa Tompobulu Resort Balocci Taman Nasional Bantimurung Bulusaraung - Hilmiah, Hilmiah; Hiola, St. Fatma; Wiharto, Muh. (bionature, 2017)
Abstract. Resort Balocci of Bantimurung Bulusaraung National Park is location grown many natural orchids. This research aims to knew the natural orchids species. This research used the exploration method by tracing did the study area investigation and documentation includes of took the picture and morphological characterization as basic to identification of orchids type. Exploration of natural orchid conducted in 1 location with 94 distribution point had height from 764 m dpl until 1252 m dpl. The results of research got 44 types of orchid, the research there were 3 kinds of orchids growth characteristic, epiphytic amount 38, terrestic 5, and litofit 2, while the type its growth dominated by simpodial orchid amount 26 types. Type many found that was Eulophia spectabilis. Based on the height of place, type grow in higher position was Trichotosia sp that is 1252 m dpl while lower position was Bulbophyllum sp.2, Dendrobium stuartii, Oberonia sp.1, Pholidota sp.2, dan Luisia sp.1 that is 764 m dpl. Based on light intensity visually, the most commonly found orchid in the light intensity is half as much as 35. Keywords: Natural orchids, Epiphytic, Resort Balocci, Bantimurung Bulusaraung National Park Area